Direct-from-whole-blood testing will speed sepsis diagnosis - Lowery, Thomas J (MLO. Medical laboratory observer, 2018)
In a recent study published in the Journal of Antimicrobial Chemotherapy, investigators at Lee Health found that patients with potentially deadly infections received targeted therapy 28 hours faster with direct-from-whole-blood tests.2 Using the FDA-cleared direct-from-whole-blood fungal panel, the lab also contributed to the hospital's cost stewardship initiatives and drove savings for the hospital, because faster negative results reduced unnecessary antimicrobial therapy by an average of four days and an estimated cost saving of $280 per patient. Studies have demonstrated that up to 40 percent of patients with bloodstream infections received ineffective empiric therapy.6 The consequences of overuse of unnecessary antimicrobials are significant, from the rise of frightening drug-resistant superbugs identified by the Centers for Disease Control and Prevention (CDC) to immediate patient health impacts such as toxicity. Enterococcus faecium, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus.8 In a prospective pivotal trial that included 11 centers and more than 1,400 subjects, test results were achieved 2.5 days faster than with blood culture with excellent accuracy, including overall average sensitivity of 90 percent and overall average specificity of 98 percent.